Giant Faraday Rotation through Ultrasmall Fe0n Clusters in Superparamagnetic FeO-SiO2 Vitreous Films - Nakatsuka, Yuko; Pollok, Kilian; Wieduwilt, Torsten; Langenhorst, Falko; Schmidt, Markus A.; Fujita, Koji; Murai, Shunsuke; Tanaka, Katsuhisa; Wondraczek, Lothar (Advanced Science, 2017)
Magnetooptical (MO) glasses and, in particular, Faraday rotators are becoming key components in lasers and optical information processing, light switching, coding, filtering, and sensing. The common design of such Faraday rotator materials follows a simple path: high Faraday rotation is achieved by maximizing the concentration of paramagnetic ion species in a given matrix material. However, this approach has reached its limits in terms of MO performance; hence, glass-based materials can presently not be used efficiently in thin film MO applications. Here, a novel strategy which overcomes this limitation is demonstrated. Using vitreous films of xFeO·(100 − x)SiO2, unusually large Faraday rotation has been obtained, beating the performance of any other glassy material by up to two orders of magnitude. It is shown that this is due to the incorporation of small, ferromagnetic clusters of atomic iron which are generated in line during laser deposition and rapid condensation of the thin film, generating superparamagnetism. The size of these clusters underbids the present record of metallic Fe incorporation and experimental verification in glass matrices.
CRIS-Team Scopus Importer:2023-04-20
Keywords: amorphous oxides; magnetooptics; ultrasmall metallic particles